Pengaruh Desain Sistem Pembelajaran Dan Teknik Komunikasi Guru Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas VIII Di MTs Al Mahrusiyah Lirboyo Kota Kediri - Hikmatun Nafi'ah; Adibussholeh HM (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
In the world of education, of course the learning process also takes place, and the learning process requires the right method. Mistakes using the method, can hinder the achievement of desired educational goals. In fact, education shows that students play a more important role as objects and teachers act as subjects. The information center or learning center is the teacher, so it often happens students will learn if the teacher teaches. In this study using contextual learning compared with conventional learning. In addition to learning methods communication techniques are also needed to support the success of students. In this study using quasi quantitative research methods, with ANCOVA analysis techniques. Overall contextual learning is superior compared to conventional learning and teacher communication techniques affect learning outcomes with sig values. 0,000 ≤ 0.05.